Micro-fragmented Adipose Tissue Transplantation (MATT) for the treatment of acetabular delamination. A two years follow up comparison study with microfractures. - Ivone, Alessandro; Fioruzzi, Alberto; Jannelli, Eugenio; Castelli, Alberto; Ghiara, Matteo; Ferranti Calderoni, Enrico; Fontana, Andrea (Acta Biomedica Atenei Parmensis, 2019)
Background: Delamination of acetabular articular cartilage is a common progressive abnormality in hips with femoroacetabular impingement. The aim of this study is to compare the effectiveness of two different procedures for the arthroscopic treatment of acetabular delamination: microfractures (MFx) and micro-fragmented autologous adipose tissue transplantation (MATT) technique. Methods: We carried out a controlled retrospective study of 35 patients affected by an acetabular cartilage delamination in femoroacetabular impingement (FAI). In all the selected cases the size of the defect ranged from 1 to 2 cm2, with a mean size of 1.9 cm² in MFx group and 1.6 cm² in MATT group (p=0.1). Of these, 18 patients were treated with MFx while 17 patients were treated with MATT. The two groups were similar in terms of clinical, functional and radiological aspects. All the patients were assessed before and after the procedure, for pain and function, with the modified Harris Hip Score (mHHS). The mean preoperative mHHS was 50±5 for MFx group and 53±6 for MATT group (p = 0.245). All the patients were followed-up for two years. Results: The final mHHS was 76±12 in MFx group and 97.1±3 in MATT group (p<0.001). In both groups neither a conversion to total hip arthroplasty nor a revision hip arthroscopy was observed. Conclusions: The results of this study provide proof that MATT technique improves clinical outcomes with a mHH scoring significantly higher than MFx group.